Narratives of science in the history research article (De Signos y Sentidos, 2025)
In studies focused on scientific-academic discourse, the history research article has received little attention in terms of their specificity. This article aims to characterize this type of text and develop an approach for its analysis. To achieve this goal, the article examines the emergence of scientific texts in the context of the formation of modern science, identifies tensions between the narrative nature of academic historical discourse and the argumentative and expositional requirements of the scientific domain, and introduces the notion of “narrative of science”. This concept is addressed from a semiotic-discursive perspective that incorporates contributions from Actor-Network Theory, semiotics, and rhetorical studies on scientific texts, focusing on the rhetorical-discursive mechanisms present in history research articles. The article concludes with the illustration of this approach through the analysis of a recent Argentine history article. In particular, it focuses on the discursive configuration of three situational references –situation of enunciation, series of events, and situation of research– their articulations, and their implications for the production of scientific-academic credibility. In this way, this study seeks to provide a deeper understanding of the nature and functioning of history research articles as communicative forms.
Keywords: history research article; scientific-academic discourse; narrative of science; economies of credibility; recent history